Application of millisecond pulsed laser for thermal fatigue property evaluation. (1st February 2018) - Pan, Sining; Yu, Gang; Li, Shaoxia; He, Xiuli; Xia, Chunyang; Ning, Weijian; Zheng, Caiyun
Highlights: A novel thermal fatigue approach using millisecond pulsed laser is proposed. Low pulse repetition rate and high pulse energy induces small thermal oscillation. High pulse repetition rate and low pulse energy produces large thermal shock. The method can be applied to evaluate thermal fatigue property of engine parts. Abstract: An approach based on millisecond pulsed laser is proposed for thermal fatigue property evaluation in this paper. Cyclic thermal stresses and strains within millisecond interval are induced by complex and transient temperature gradients with pulsed laser heating. The influence of laser parameters on surface temperature is studied. The combination of low pulse repetition rate and high pulse energy produces small temperature oscillation, while high pulse repetition rate and low pulse energy introduces large temperature shock. The possibility of application is confirmed by two thermal fatigue tests of compacted graphite iron with different laser controlled modes. The developed approach is able to fulfill the preset temperature cycles and simulate thermal fatigue failure of engine components.